1964
DOI: 10.1085/jgp.47.5.879
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Na Concentration on Na Transport across Frog Skin

Abstract: AB ST R A C T The effects of changes in Na concentration of the bathing solutions on some transport and permeability properties of the isolated frog skin have been examined. Rate coefficients for unidirectional Na movements across the two major barriers in the skin have been estimated as functions of Na concentration. The results indicate that the "apparent Na permeability" of the outer barrier of the skin decreases markedly when Na concentration in the outer solution is increased from 7 to 115 mM.The observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
70
0

Year Published

1966
1966
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(88 citation statements)
references
References 10 publications
18
70
0
Order By: Relevance
“…Kirschner (9) found that shortcircuit current across frog skin rose by increasing sodium concentration, reached a maximum at about 35 meq/liter of external Na and then decreased as the concentration was raised further. Cereijido et al (1) interpreted the saturation of the rate of sodium transport in Rana pipiens with increasing external Na concentration as due, in part, to changes in the permeability of the outer membrane rather than to saturation of the transporting system ("pump") itself. Cirne and Malnic (2) observed that short-circuit current in the toad skin of Bufo paracnemis and Bufo ictericus could be fitted in the range of 5-50 meq/liter external Na concentration by Michaelis-Menten kinetics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kirschner (9) found that shortcircuit current across frog skin rose by increasing sodium concentration, reached a maximum at about 35 meq/liter of external Na and then decreased as the concentration was raised further. Cereijido et al (1) interpreted the saturation of the rate of sodium transport in Rana pipiens with increasing external Na concentration as due, in part, to changes in the permeability of the outer membrane rather than to saturation of the transporting system ("pump") itself. Cirne and Malnic (2) observed that short-circuit current in the toad skin of Bufo paracnemis and Bufo ictericus could be fitted in the range of 5-50 meq/liter external Na concentration by Michaelis-Menten kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Initial point of each period is indicated by letters (A, before block of Na transport and B, after block of Na transport). 1 (0.60 < P < 0.70, n = 10, paired t test). LNarA(before) = 102.7…”
Section: Active Sodium Transport and Oxygen Consumption As A Functionmentioning
confidence: 97%
“…It seems more reasonable to postulate a carrier mechanism at the outer surface, which may well saturate at a fairly low level of concentration of Na in the outer bathing medium. Cereijido et al (1964) discuss such mechanisms in relation to their provocative and precise measurements on the effects of Na concentration on Na transport across isolated bits of frog skin. …”
Section: Discussionmentioning
confidence: 99%
“…As explained above, the size of L. ocellatus does not permit the study of paired samples of skins from the same animal. 22Na uptake When 22Na was added to the outer bathing solution the influx of 22Na reached equilibrium in less than 20 min (Hoshiko & Ussing, 1960;Curran et al 1963;Cereijido, Herrera, Flanigan & Curran, 1964;Cereijido & Rotunno, 1967). It can be demonstrated that by the time the influx of 22Na equilibrates, the Na transporting compartment should have its 22Na-specific activity in a steady state (Solomon, 1960).…”
Section: Na Influxmentioning
confidence: 99%
“…Hence the number of counts per minute of 22Na in the epithelium divided by the specific activity of 22Na in the outer chamber can be taken as an estimate of the amount of Na in the transporting compartment, in particular if, as it is the case in the present paper, only comparative studies are intended. There is a relationship between the amount of Na in this compartment and the rate of Na pumping Cereijido et al 1964). It was suggested Crabbe & de Weer, 1965), that the increase in Na permeability of the outer barrier elicited by ADH, produces a rise in the concentration of Na in the transporting compartment, and that the Na pump located at the inner 126 ADH EFFECT ON Na INFLUX1 barrier reacts to this rise in concentration by pumping more Na toward the inside.…”
Section: Na Influxmentioning
confidence: 99%